The intervention dilemma and high burden of children with autism in Guizhou province, Southwest China - Liu, Ye; Zhou, Fang; Qin, Jixuan; Lin, Yong; Li, Tonghuan; Zhu, Chengyong; Long, Fang; Wang, Xike; Hu, Xiao; Zhou, Hao (Frontiers in Psychiatry, 2022)
Background Autism spectrum disorder (ASD) is a highly disabling disease, and the disease burden is high. Data on disease burden are limited in China, especially in the Southwest. Therefore, the aims of this study were to investigate the intervention status and disease burden of children with autism in Southwest China. Methods Families of children with ASD were recruited from hospitals, special education schools, and private rehabilitation centers; they participated in the survey and completed the questionnaire. Descriptive analysis was conducted on the questionnaire results, including basic demographic characteristics, rehabilitation status, and disease burden. Multivariate analysis was used to analyze the association of the family’s basic demographic characteristics and rehabilitation status and costs of ASD. Results A total of 231 ASD families participated in this survey, and 78.35% (181/231) of ASD children were male. The mean age was 4.34±2.09 years. A total of 55.84% (129/231) of ASD children had intellectual disability. Only 46.32% (107/231) started receiving intervention within 1 month after diagnosis. The institutions for ASD children’s rehabilitation intervention were mainly tertiary hospitals (39.39%), special education schools (29.87%) and private rehabilitation institutions (21.64%). For a total of 42.86% (99/231) of the ASD children, the duration of intervention was less than 10 hours per week. A total of 74.89% (173/231) of ASD children received rehabilitation intervention at home. A total of 66.67% of parents were satisfied with treatment. The monthly cost of medical intervention for autistic patients was 7225±474 RMB ($1134±74), and the nonmedical intervention cost was 2133±107 RMB ($334±17). The annual disease burden of autistic patients was 86,700 ± 5,688 RMB ($13596±892). The estimated annual disease burden of ASD was RMB 5.548 billion ($870 million) in Guizhou Province. Conclusions The results revealed that the rehabilitation resources were limited and that the disease burden of ASD was high in Guizhou Province; therefore, improving the rehabilitation status and easing the disease burden of children with ASD is urgent in these regions.